1981
DOI: 10.2172/6673597
|View full text |Cite
|
Sign up to set email alerts
|

Research in the Geysers-Clear Lake geothermal area, northern California

Abstract: DE82 905361 COVER View southeastward at geothermal development in the Geysers steam field. Large steam plumes rise from condensing towers of numerous electrical powerplants: smaller plumes rise from geothermal wellheads. Northwest-flowing Big Sulphur Creek has excavated the canyon that transects the photograph from upper right to lower left. Hydrothermal leakage from the steam reservoir occurs dong faults that cut rocks of the Franciscan assemblage along the northeast side of Big Sulphur Creek canyon. The alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The low‐ V p / V s anomaly observed at The Geysers correlates with the volume where the pore fluid is thought to be vapor‐dominated, where pore pressure is relatively low and argillaceous minerals relatively dry [e.g., McLaughlin , 1981]. Julian et al [1996] concluded that The Geysers might have had an associated low‐ V p / V s anomaly prior to development, since such conditions probably existed naturally then.…”
Section: Discussionmentioning
confidence: 99%
“…The low‐ V p / V s anomaly observed at The Geysers correlates with the volume where the pore fluid is thought to be vapor‐dominated, where pore pressure is relatively low and argillaceous minerals relatively dry [e.g., McLaughlin , 1981]. Julian et al [1996] concluded that The Geysers might have had an associated low‐ V p / V s anomaly prior to development, since such conditions probably existed naturally then.…”
Section: Discussionmentioning
confidence: 99%
“…However, this argument does not seem to apply to the Coast Ranges because initiation of volcanism at 2.6-2.0 Ma in the Clear Lake area lagged behind passage of the Mendocino triple junction by only 0.7 to 1.3 m.y. (Donnelly-Nolan and others, 1981;McLaughlin, 1981;McLaughlin and others, 1985b ). This shorter lag may be attributable to the likelihood that thermal anomalies in the upper 10 km of crust above the slabless window (slab gap) are more directly tied to extensional strain adjacent to newly lengthened segments of the transform than to conductive heat transfer.…”
Section: -To 24-ma Neenach Volcanicsmentioning
confidence: 97%
“…1). During the Late Mesozoic (Franciscan) to Early Tertiary, this region was the site of deep oceanic sedimentation, northeast-directed subduction, and regional metamorphism, which locally grades up to the blueschist facies (McLaughlin, 1981). Modern hydrothermal activity at The Geysers and in the surrounding area is associated with shallow intrusions related to the Pliocene to Recent Clear Lake volcanic field .…”
Section: Geologic Relationshipsmentioning
confidence: 99%
“…Most of the steam is produced from a thick succession of metagraywacke that underlies a chaotic suite of serpentinite, argillite, cherts, and greenstone. Excellent reviews of the geologic and geophysical features of the area can be found in McLaughlin and Donnelly-Nolan (1981) and Donnelly-Nolan et al (1993).…”
Section: Geologic Relationshipsmentioning
confidence: 99%